Pengaruh Antara Pendidikan Orang Tua dan Tipe Kepribadian Anak dengan Perilaku Bullying di Sekolah - Danang Pamungkas; Imam Makruf (Cendekia: Jurnal Pendidikan dan Pembelajaran)
The school environment, apart from being able to expand the world of children, can also be a place for bad psychic development that can interfere with children's development, one of which is violence between students or bullying. This study aims to determine the effect of parental education on student bullying behavior, determine the effect of student personality type on bullying behavior, and determine the effect of parental education and student personality on student bullying behavior in schools. The population of this study was 1,340 students with a sample of 303 students who were taken using simple random sampling technique. Data on parents' education, children's personality, and bullying behavior were collected using a questionnaire. Hypothesis testing using single regression and multiple regression. The results showed: 1) There was a relationship between parental education and bullying behavior with a significance value of 0.000 <0.05, the contribution of parents' education was 55.0% with the regression equation Y = 75,773+8,963X1. 2) There is a relationship between the child's personality and bullying behavior with a significance value of 0.000 <0.05. The contribution of the child's personality is 83.9% with the regression equation Y = 20.298+1.123X2. 3) There is a significant relationship between parental education and children's personality with bullying behavior with a probability of 0.000 < 0.005. The contribution of these two variables is 87.4% with the regression equation Y' = 26,318+2,996 +0,924.